2015
DOI: 10.1080/19443994.2014.923209
|View full text |Cite
|
Sign up to set email alerts
|

Is a costly river restoration project beneficial to the public? Empirical evidence from the Republic of Korea

Abstract: Public water supply service is to provide certain guaranteed level of quantity and quality in any given circumstances. In this regard, public water supply service treated as public goods that either central or state authority governs for good intentions. Growing concerns about water scarcity in national level due to its vulnerability on climate change lead public to suppress economic burden. In fact, Korean government has had a similar concern bringing to construct 16 weirs in the four major rivers. This const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…The purposes of those two projects are to ameliorate water quality, increase water quantity, and restore ecosystem services. Although many ex ante economic feasibility studies often concluded that the social welfare is always positive [35], ex post analysis may be needed for those sites to re-examine their benefits since they are built by public investment.…”
Section: Discussionmentioning
confidence: 99%
“…The purposes of those two projects are to ameliorate water quality, increase water quantity, and restore ecosystem services. Although many ex ante economic feasibility studies often concluded that the social welfare is always positive [35], ex post analysis may be needed for those sites to re-examine their benefits since they are built by public investment.…”
Section: Discussionmentioning
confidence: 99%
“…It was the costliest construction projects in recent Korean history [12]. The total budget for this mega project was approximately $17.3 billion dollars, but Lee et al [5] concluded that the economic value created by the project was extremely smaller than its cost. This might be the result of the failure of reflecting various stakeholders' demands and desires of water value or ignoring the trend of river restoration concept in terms of sustainability.…”
Section: The Four Major Rivers Restoration Projectmentioning
confidence: 99%
“…The main purpose of this mega project is to prevent flood, to capture sufficient water resources, to improve water quality, and to increase total water volume up to 1.3 billion cubic meters [4]. In spite of these good intentions, Lee et al [5] pointed out that policy makers excessively overused public expenditure and ignored various stakeholders' water demand related to it values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of evolving challenges in the water sector, it is believed that the measures implemented through the FMRRP were not adequately coupled to the long-term objectives of the Strategy, and that the possible contribution of forest hydrological services to sustainable water management was underestimated. According to various stakeholders, the operations of the FMRRP of dredging sediment, installing riverbed filtration facilities, and installing weirs and dams did not entirely follow the principles of green growth, neither at the environmental, nor at the economical, nor at the political level [82][83][84][85][86]. Park (2010) [87] stated that the FMRRP likely induced some habitat destruction.…”
Section: Inclusion Of Key Forest Hydrological Services In the Sustainmentioning
confidence: 99%